2013
DOI: 10.3109/17549507.2013.831484
|View full text |Cite
|
Sign up to set email alerts
|

The assessment for living with aphasia: Reliability and construct validity

Abstract: (2003) and Cruice, Hill, Worrall, and Hickson (2010) identifi ed factors such as engaging in meaningful activities, socializing with others, and having a positive outlook as aspects of QoL in aphasia. Additionally, there is increased awareness that improvements in a clinical setting do not necessarily result in improvements in daily life situations or life satisfaction; thus, there has been a call for interventions that positively and directly affect life quality (Cruice et al., 2003(Cruice et al., , 2005Holla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 42 publications
1
42
0
3
Order By: Relevance
“…Aphasia-related quality of life was assessed with the Assessment of Living with Aphasia (ALA; Simmons-Mackie et al 2014). This self-report measure evaluates the impact of aphasia on five domains: language, participation, environment, personal and moving on with life.…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Aphasia-related quality of life was assessed with the Assessment of Living with Aphasia (ALA; Simmons-Mackie et al 2014). This self-report measure evaluates the impact of aphasia on five domains: language, participation, environment, personal and moving on with life.…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…)? Does therapy improve quality of life as assessed by the Assessment of Living with Aphasia (Simmons‐Mackie et al . )?…”
Section: Introductionmentioning
confidence: 99%
“…For example, Communication Activities of Daily Living is available in Italian, Japanese and some variations of Spanish (Spreen & Risser, 2003). The same is true for the Assessment for Living with Aphasia (Kagan et al, 2010;Simmons-Mackie et al, 2014), which is a pictographic, self-report measure of aphasia-related QOL, that has been designed in large measure to be culture free. Currently, several aphasia tests developed in English have been translated and adapted into Korean, such as the Frenchay Aphasia Screening Test (FAST), Western Aphasia Battery (WAB), and Boston Naming Test.…”
Section: Introductionmentioning
confidence: 92%
“…Results also suggested that SLPs were assessing QoL with similar patterns of frequency across severity levels and aphasia type (Table 2). Those with a moderate level of aphasia severity were administered QoL assessments most often as 57 of 61 responses (93%) indicated that these individuals were assessed quite often (25) or very often (32). The least likely to be assessed were those with profound aphasia, with 16 (26%) and 29 (47.5%) of 61 responses indicating that assessments were given quite often or very often, respectively.…”
Section: Assessment Of Quality Of Lifementioning
confidence: 99%